Basic Life Support Guidance for Caregivers of NICU Graduates: Evaluation of Skill Transfer after Training - Benedict, Aswathy; Pournami, Femitha; Prithvi, Ajai Kumar; Nandakumar, Anand; Prabhakar, Jyothi; Jain, Naveen (Journal of Child Science, 2022)
Background Intensivists indeed discharge neonatal intensive care unit (NICU) graduates after a period of physiological stability. There is, however, a real risk of life-threatening events at home. Survival after such episodes depends on time from arrest to initiation of basic life support (BLS). It is rational to train parents who would be first responders. We sought to measure objectively and prospectively, effect of BLS training on parents of NICU graduates on the psychomotor, cognitive, and affective domains of human learning.Methods After face-to-face training sessions, proportion of home caregivers who obtained 100% marks on a pretested performance checklist for psychomotor skills of BLS on a mannequin were measured. Two other domains of learning and number of attempts required to obtain desirable results were also analyzed.Results Median (interquartile range [IQR]) birth weight of the high-risk neonates was 1,050 g (930, 1570) and median gestational age was 29 (IQR 28, 33) weeks. More than 75% of parents had no prior exposure to BLS training. Among 46 trained caregivers, 80.4% achieved the desired score of 5 in the psychomotor performance checklist on the first attempt. A maximum of two attempts was required to reeducate and achieve score of 5 in the remaining caregivers. Forty-two (91.3%) caregivers obtained full marks on cognitive domain test. All caregivers responded positively toward affective domain questionnaire.Conclusion It is possible to train parents in BLS measures and demonstrate their psychomotor skills on a mannequin effectively. No parents who were approached refused training or indicated anxiety in learning the skills required.
Keywords: basic life support; preterm; out of hospital arrests; domains of learning